The influence of selected factors on the perceptions of managers of medium business firms regarding legal firms - M. Tait; M. Tait; S. M. Van Eeden (South African Journal of Business Management, 2000)
The South African service provider is faced with an increasingly turbulent and complex competitive environment. Factors which impact specifically on the environment of service firms include the growing importance of consumerism and a drastic increase in competition. A factor that impacts directly on the growing competition amongst providers of legal services is the increase in law graduates and commensurate increase in qualified attorneys and advocates entering the market. This article represents an exploratory study establishing the relative value attached by medium business in South Africa to certain factors pertaining to firms providing legal services.
Keywords: 650